Biomedical devices : design, prototyping, and manufacturing - Özel, Tuğrul, 1967-; Bártolo, Paulo; Ceretti, Elisabetta, 1966-; Ciurana Gay, Joaquim De; Rodriguez, Ciro Angel, 1967-; Silva, Jorge Vicente Lopes da, 1963- (Wiley, 2016)
Biomedical Devices: Design, Prototyping, and Manufacturing features fundamental discussions of all facets of materials processing and manufacturing processes across a wide range of medical devices and artificial tissues.-Represents the first compilation of information on the design, prototyping, and manufacture of medical devices into one volume -Offers in-depth coverage of medical devices, beginning with an introductory overview through to the design, manufacture, and applications -Features examples of a variety of medical applications of devices, including biopsy micro forceps, micro-needle arrays, wrist implants, spinal spacers, and fixtures -Provides students, doctors, scientists, and technicians interested in the development and applications of medical devices the ideal reference source.